Cobalt Sulfide Nanowires Core Encapsulated by a N, S Codoped Graphitic Carbon Shell for Efficient Oxygen Reduction Reaction. Issue 17 (3rd April 2018) - Han, Ce; Li, Qun; Wang, Dewen; Lu, Qingqing; Xing, Zhicai; Yang, Xiurong
Abstract: Exploration of economical electrocatalysts for highly efficient and stable oxygen reduction reaction (ORR) is believed to be essential for diverse future renewable energy applications. Herein, cobalt sulfide nanowire core encapsulated in a N, S codoped graphitic carbon shell (CoS NWs@NSC) is successfully fabricated via the calcination of polydopamine‐coated Co(CO3 )0.5 (OH)0.11 H2 O NWs with sulfur powder under argon atmosphere. The uniform encapsulation of CoS core by N, S codoped graphitic carbon shell favors the interaction of the core–shell structure for generating stable and numerous ORR active sites homogeneously dispersed throughout the materials. Meanwhile, the wire‐like CoS NWs@NSC stacks to form 3D mesoporous conductive networks, which improves the mass and charge transport capability of catalyst. Accordingly, the resultant CoS NWs@NSC electrocatalysts possess excellent ORR activity through the four‐electron pathway with superior stability and methanol tolerance over the Pt/C in 0.1m KOH. This strategy can offer inspiration for designing and fabricating novel core–shell‐structured nanomaterials with active sites derived from uniform morphology as potential electrocatalysts for various vital renewable energy devices. Abstract : Cobalt sulfide nanowires core encapsulated by a N, S codoped graphitic carbon shell is successfully fabricated as a high‐performance electrocatalysts for the oxygen reduction reaction (ORR). It features 3D conductive mesoporous networks with abundant uniform ORR active sites and has excellent ORR performance through a four‐electron pathway with superior stability and methanol tolerance over the Pt/C in alkaline media.